Description of two new species belonging to the genus Deltocephalus Burmeister (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) from India - Chalam, M. S.v.; Rao, V. Ramasubba (Zootaxa, 2005)
Two new species, Deltocephalus (Recilia) delongi and Deltocephalus (Recilia) parapruthii, of the genus Deltocephalus Burmeister from India are described and illustrated.